Stakeholder Perceptions and Institutional Readiness for Inclusive Education Implementation: A Multi-Dimensional Analysis - Octa Vian Dwi Tanto; Muh. Yamin (Journal of Early Childhood Education Perspectives, 2025)
Inclusive education implementation in Indonesia's regional cities faces significant challenges, particularly in bridging conceptual support with practical readiness. This study examines multi-dimensional public perceptions toward inclusive education in Palopo City, South Sulawesi, analyzing the relationship between conceptual understanding, implementation support, institutional readiness, and perceived benefits. A cross-sectional survey design was employed with 26 purposively selected stakeholders using a validated 30-item Likert scale questionnaire (Cronbach's α = 0.89). Data were collected during May-June 2024 and analyzed using descriptive statistics, mean comparison tests, and dimensional analysis. Findings revealed significantly high conceptual understanding (M = 4.115, SD = 0.654) and strong support for inclusive education principles (M = 4.423, SD = 0.631). However, institutional readiness showed concerning gaps, particularly in facility adequacy (M = 3.000, SD = 0.832) and teacher competency perceptions (M = 3.346, SD = 0.829). Dimensional analysis indicated substantial discrepancies between theoretical support (Conceptual Understanding: 4.115) and practical implementation readiness (Institutional Readiness: 3.476, p < 0.05). While Palopo City stakeholders demonstrate robust conceptual support for inclusive education, critical implementation gaps exist in institutional infrastructure and human resource preparedness. These findings suggest urgent need for comprehensive capacity-building interventions targeting teacher training, facility enhancement, and systematic implementation support mechanisms.